Development of Softplc Module Testing Methodology - Abdullaev Sardor Alisherovich; Yuldoshev Mirzobek Nurilloevich (Zien Journals, 2022)
The article covers methodology for testing SoftPLC module included in “AxiOMA Control” CNC system, implemented by creating a package of test programs in the FBD language, and test program algorithm has been developed.
Keywords: PLC program; programmable logic; controller